Knowledge brokering pivotal in professional learning: quality use of research contributes to teacher-leaders’ confidence - Friesen, Sharon; Brown, Barbara (Frontiers in Education, 2024)
Educational networks and knowledge brokering play a critical function in supporting educators to keep abreast of scholarly literature and contemporary research that inform practice and policy in schools and districts. In this article, we leverage a quality use of research-evidence framework within a design-based study to elucidate the pivotal role of knowledge brokering in how teacher leaders utilized research during their participation in a professional learning series. In a survey administered to K-9 teacher leaders in Western Canada at the end of a year-long professional learning series, participants (n = 374/500) provided their reflections about how the series supported their learning. The analysis revealed developments across individual, organizational, and system-level components. A significant contribution of this study is that meaningfully integrated research evidence in professional learning can support teacher leaders' individual confidence in practice, confidence in collaboration at the school level, confidence in leading professional conversations at the organizational level, and confidence in staying updated with educational research at the system level fostering a culture of support and continuous improvement. Knowledge brokering is a pivotal function of relational professional learning networks and when embedded in design-based professional learning for teacher leaders, this powerful combination can contribute to quality research use and can serve to strengthen the theory-to-practice connections in educational contexts.